60. The effect of cerebellar degeneration on human sensori-motor plasticity. Issue 4 (April 2016) - Dubbioso, R.; Pellegrino, G.; Antenora, A.; De Michele, G.; Filla, A.; Santoro, L.; Manganelli, F.
Abstract : We investigated how cerebellar degeneration influences the plasticity of the tprimary motor cortex (M1) by using PAS (paired associative plasticity) technique. PAS involves repeated pairs of electrical stimuli to the median nerve and transcranial magnetic stimuli of the motor cortex. If the interval between peripheral and cortical stimulation is around 21–25 ms, corticospinal excitability is increased via a long-term potentiation (LTP)-like effect within M1. Our aims were: (i) to explore the presence of a time-specific influence of cerebellar degeneration on human associative plasticity; (ii) to evaluate the role of the somatosensory pathway on the cerebellar modulation of sensory-motor plasticity. We studied 10 patients with pure cerebellar atrophy and 10 age-matched healthy subjects. Motor evoked potentials amplitudes, short-afferent inhibition, motor thresholds, I/O curves, somatosensory-evoked-potentials (SEPs) were measured before, just after and 30 min after PAS at interstimulus intervals of 21.5 and 25 ms. In cerebellar patients, LTP-like effect induced by PAS was abolished at 25 ms, but not at 21.5 ms. SEPs showed that the P25 wave amplitude was markedly reduced in patients with a more severe clinical and radiological impairment of the cerebellum. Patients with cerebellar atrophy have an altered capability to process time-specific sensory volleys, influencing the M1 plasticity.